Comparison of Early In-Hospital Outcomes between Minimal Manipulation and Maximal Fielding during Primary PCI and its Impact on TIMI Flow - Khan, Ismail; Khattak, Zahoor Aslam Khan; Khan, Muhammad Nadir; Hasan, Maria; Jaffri, Syed Khawar Abbas; Samore, Naseer Ahmed; Shahzad, Syed Khurram (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the association between minimal and maximal manipulation and slow/no flow during Primary Percutaneous Coronary Intervention (PPCI) and its associated outcomes.Study Design: Analytical, Cross-Sectional study.Place and Duration of Study: Armed Forces Institute of Cardiology/National Institute of Heart Diseases, from Mar to May 2023Methodology: Total 189 patients were enrolled through non-probability consecutive sampling in the present study. STElevation Myocardial Infarction (STEMI) patients irrespective of age and gender were included. Patients were grouped into minimal and maximal manipulation groups and subsequently PPCI was proceeded. During procedure, TIMI-flow grading was assessed and patients were further grouped into no flow (TIMI-0 or 1), slow flow (TIMI-2) and normal flow(TIMI-3) group. Outcome variables including TIMI-flow, arrhythmia, Heart Failure (HF) and in-hospital mortality were observed. Chi-square test and student t-test were applied and p-value 0.05). Frequency of mortality was higher in maximal manipulation group 7(7.4%). In relation to reflow; diabetes, multiple pre-stenting balloon inflation and multiple post-stenting balloon inflation, and type of arrhythmia were significantly ...................Conclusion: There was no role of minimal and maximal manipulation in developing slow flow/no flow during primaryPCI.